¿Cómo han vivido los adultos mayores la pandemia COVID-19? (2021)
On March 14, 2020, the Spanish Government declared a state of alarm throughout the country in the face of the uncontrolled spread of COVID-19. The Spanish population was forced into strict confinement and, over time, the restrictions were gradually eased and the country started a new normality. For months, there were different measures to avoid face-to-face social interactions and infection. Certainly, the social group that suffered most from the pandemic and the restrictions imposed was the elderly. The research presents official quantitative data and interviews with people knowledgeable about the subject. Confinement and subsequent restrictions had an uneven impact; many older adults have suffered the consequences in loneliness and anonymity. There is still a lack of studies to know in-depth their experiences, opinions, reflections, and possible discomforts experienced during the pandemic.